FACTORS THAT INFLUENCE THE PERFORMANCE OF MSMES IN THE CITY OF BATAM - Wijaya, Andi; Chen, David (International Journal of Application on Economics and Business, 2024)
The aim of this study is to examine whether technology, organization, and environment can influence the adoption of social media by SMEs in Batam City, and how this adoption can impact SMEs' performance. The research also investigates the effects of technology, organization, and environment on SMEs' performance in Batam City. The study population consists of SME owners in Batam City, with a sample size of 100 respondents selected using non-probability purposive sampling, focusing on SMEs using social media. SmartPLS 3.0 software was utilized for data analysis. The findings indicate that there is no significant positive influence of technology on social media adoption. However, organization and environment have a positive and significant impact on social media adoption. Social media adoption, in turn, positively and significantly affects SMEs' performance. Additionally, while technology has a positive but insignificant influence on SMEs' performance, organization and environment significantly contribute to SMEs' performance. Nonetheless, there is no significant mediating effect of social media between technology, environment, and organization. The results of this study are expected to benefit SME owners in Batam City and help improve their business performance in the current market conditions.